ANALYSIS OF LEADING SECTORS AND THEIR EFFECT ON ECONOMIC GROWTH IN JEMBRANA REGENCY - Ni Kadek Oki Selmanita; Ida Bagus Putu Purbadharmaja (Adisam Publisher, 2025)
Regional economic growth is an important indicator for evaluating development performance. This study analyzes leading sectors and examines the effect of the agriculture, forestry, and fisheries sector, as well as the transportation and warehousing sector, on economic growth in Jembrana Regency, with the Labor Force Participation Rate (LFPR) as a moderating variable. This study uses secondary data, including the Gross Regional Domestic Product (GRDP) of Jembrana Regency and Bali Province, as well as labor statistics from the Central Bureau of Statistics (BPS) for the period 2010–2024. The methods used are Location Quotient (LQ), descriptive analysis, multiple linear regression, and Moderated Regression Analysis (MRA). The results show that the agriculture, forestry, and fisheries sector, as well as the transportation and warehousing sector, are categorized as leading sectors in Jembrana Regency. Simultaneously, these two sectors have a significant effect on economic growth. Partially, the agriculture, forestry, and fisheries sector has a positive and significant effect, while the transportation and warehousing sector also provides a positive contribution. The moderation analysis reveals that the LFPR strengthens the effect of the transportation and warehousing sector on economic growth but does not moderate the relationship between the agriculture, forestry, and fisheries sector and economic growth. These findings suggest that the local government should strengthen the productivity of base sectors, particularly agriculture and transportation, and enhance labor force participation to support sustainable economic growth in Jembrana Regency.